The Effect of the Bamboozle Game on the Reading Ability of Seventh-Grade Students at SMP Muhammadiyah 1 Lubuklinggau - Ningsih, Anggara; Sujarwati, Iis (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study examines the effect of the Bamboozle game on students’ reading ability, aiming to enhance engagement and comprehension through innovative and interactive learning methods.Method – A pre-experimental research design was employed, involving one seventh-grade class at SMP Muhammadiyah 1 Lubuklinggau in the 2024/2025 academic year. A total of 33 students participated, with purposive sampling selecting 10 students for detailed analysis. Data were collected using pre-tests and post-tests to measure improvements in reading comprehension. Findings – The results indicate a significant improvement in students’ reading comprehension, as reflected in the increase in the post-test mean score to 82.7. The calculation of Cohen’s effect size (d = 1.40) confirms a large effect, highlighting the effectiveness of the Bamboozle game in enhancing reading skills. The findings reveal that students showed notable progress in vocabulary acquisition, identifying main ideas, and making inferences from texts. Additionally, the interactive and competitive nature of the game increased students' motivation and engagement, fostering a more dynamic and enjoyable learning environment. The study also found that students exhibited greater confidence in interpreting complex passages and demonstrated improved retention of reading materials compared to traditional methods. Research Implications – The findings highlight the potential of game-based learning in improving reading comprehension and student motivation. Institutions should consider integrating digital tools like Bamboozle into reading instruction and provide teacher training on gamified learning strategies. However, this study's small sample size and short intervention period limit generalizability. Future research should explore long-term effects and application to other language skills.